Design Optimization of Perfluorinated Liquid‐Infused Surfaces for Blood‐Contacting Applications - Jun Ki Hong; Kavya Mathur; Alexander M. Ruhoff; Behnam Akhavan; Anna Waterhouse; Chiara Neto (Advanced Materials Interfaces, 2022)
Abstract Tethered‐liquid perfluorocarbon (TLP) coatings show promise for blood‐contacting medical device applications to reduce blood adhesion and delay thrombosis. However, their fabrication and longevity under external fluid flow is not well characterized. A vapor phase silanization reaction leading to the formation of tethered‐perfluorocarbon (TP) layers containing large bumpy aggregates, 300 ± 200 nm thick, on top of an underlying 35 ± 15 nm thick uniform coating is reported. The vapor phase method compares favorably to the well‐established liquid phase deposition to reproducibly create slippery coatings on silicon and polystyrene with very low water sliding angles (2° ± 1°), without the need to control humidity conditions. The TP layer retains perfluorinated lubricants up to 20 000 s–1, using a cone‐and‐plate rheometer, with the higher viscosity lubricant perfluoroperhydrophenanthrene being more resistant to depletion than perfluorodecalin. TLP infused with either of the lubricants effectively reduces adhesion of fibrin from human whole blood relative to TP and control hydrophilic and hydrophobic surfaces. The combination of highly fluorinated TP coatings grafted from the vapor phase to create nanoscale structured surfaces infused with higher viscosity lubricant may be the most suitable combination for clinical applications of liquid‐infused surfaces to reduce thrombosis in blood‐contacting medical devices under flow.